Retrospective Analysis of Promotion of Environmental Education in Japan - Oksana Svystak-Yarotska (Pedagogical Discourse, 2015)
This article is dedicated to retrospective analysis of the development of environmental education in Japan in the second half of the 20th century – beginning of the 21st century. Approaches to the definitions «environmental education», «natural study», nature protection», «conservational education», «sustainable development» are shown. The ideas of Japanese teachers on promotive educational activities for the conservation of nature, filling content of school subjects topics related to environmental protection, resources and energy conservation, harmonizing the relationship between man and the natural environment, launching new subjects «Life Environmental Studies» and «Period of Integrated Study» are shown with the concrete examples. The article explained the role of NGOs in the activity centered on nature observation. The article also explains the retrospective development of international concepts for the role of environmental education in creating a society of sustainable development, compliance with the national development strategy and implementation of environmental education in Japan declarations of Global Conferences on environmental education and ESD.The legal basis for the implementation of environmental education in the country and the role of environmental education in the implementation of education for sustainable development are represented in «Environmental Education Law» («The Act on Enhancing Motivation on Environmental Conservation and Promotion of Environmental Education»), «Basic Policy Concerning the Enhancement of the motivation for Environmental Conservation and the Promotion of Environmental Education», «Strategy for an Environmental Nation in the 21st Century». International recognition of the achievements of Japan in Education for Sustainable Development, part of which is environmental education, is mentioned in the article.